Longitudinal assessment of climate vulnerability: a case study from the Canadian Arctic - Archer, L; Ford, J D; Pearce, T; Kowal, S; Gough, W A; Allurut, M (Sustainability Science, 2017)
The Arctic is a global hotspot of climate change, which is impacting the livelihoods of remote Inuit communities. We conduct a longitudinal assessment of climate change vulnerability drawing upon fieldwork conducted in 2004 and 2015 in Ikpiarjuk (Arctic Bay), Nunavut, and focusing on risks associated with subsistence harvesting activities. Specifically, we employ the same conceptual and methodological approach to identify and characterize who is vulnerable, to what stresses, and why, assessing how this has changed over time, including re-interviewing individuals involved in the original study. We find similarities between the two periods, with many of the observed environmental changes documented in 2004 having accelerated over the last decade, exacerbating risks of land use: changing sea ice regimes and wind patterns are the most widely documented at both times, with new observations reporting more frequent sighting of polar bear and orca. Socio-economic and technological changes have altered the context in climate change impacts are being experienced and responded to, both exacerbating and moderating vulnerabilities compared to 2004. The adoption of new technology, including GPS and widespread use of the internet, has helped land users manage changing conditions while sharing networks remain strong, despite concern noted in the 2004 study that they were weakening. Challenges around access to financial resources and concern over the incomplete transmission of some environmental knowledge and land skills to younger generations continue to increase sensitivity and limit adaptive capacity to changing climatic conditions. © 2016 Springer Japan